S-1/temozolomide versus S-1/temozolomide plus thalidomide in advanced pancreatic and non-pancreatic neuroendocrine tumours (STEM): A randomised, open-label, multicentre phase 2 trial. (December 2022) - Chi, Yihebali; Song, Lijie; Liu, Weili; Zhou, Yuhong; Miao, Yadong; Fang, Weijia; Tan, Huangying; Shi, Susheng; Jiang, Hai; Xu, Jianming; Jia, Ru; Zheng, Bo; et al.
Summary: Background: There are currently limited systemic treatment options for patients with advanced neuroendocrine tumours (NETS) and the efficacy of existing treatments is sub-optimal. We evaluated the efficacy and safety of Tegafur/gimeracil/oteracil/potassium capsules (S-1)/Temozolomide with or without thalidomide for the treatment of NETS (STEM trial). Methods: A randomised, controlled, open-label, phase 2 trial conducted at eight hospitals in China. Adults (≥18 years) with unresectable/metastatic, pancreatic or non-pancreatic NETS, with an Eastern Cooperative Oncology Group (ECOG) PS of 0–1, and progression on ≤2 previous therapies were randomised (1:1, using hierarchical block randomization with block length 4, stratified by pancreatic/non-pancreatic disease to receive S-1 40–60 mg orally twice daily on days 1–14 plus temozolomide 200 mg orally daily on days 10–14 in a 21-day cycle OR S-1 and temozolomide plus thalidomide orally nightly (100 mg on days 1–7, 200 mg on days 8–14, and 300 mg from day 15), until disease progression, death, intolerable toxicity, withdrawal of informed consent or at the investigator's discretion. The primary endpoint was objective response rate (ORR) by RECIST 1.1 in an intention-to-treat population. Safety was assessed in all patients who received treatment. The study was registered at ClinicalTrials.gov: NCT03204019 (pancreatic group) and NCT03204032 (non-pancreatic group). Findings: Between March 23, 2017 and November 16, 2020, 187 patients were screened and 140 were randomly assigned to S-1/temozolomide plus thalidomide (n = 69) or S-1/temozolomide ( n = 71). After a median follow-up of 12·1 months (IQR: 8·4–16·6), the ORR was comparable in the S-1/temozolomide plus thalidomide and S-1/temozolomide groups 26·1% [95% CI 17·2–37·5] versus 25·4% [95% CI 16·7–36·6]; odds ratio: 1·03 [95% CI 0·48–2·22]; P = 0·9381). In the S-1/temozolomide plus thalidomide group, the most common grade 3–4 treatment-related adverse event was fatigue (2/68, 3%), and in the control group were thrombocytopenia and diarrhea (both 1/71, 2%). There were no treatment-related deaths in either group. Interpretation: S-1/temozolomide with or without thalidomide leads to a comparable treatment response in patients with advanced/metastatic NETS. Funding: This work was supported by CAMS Innovation Fund for Medical Sciences (CIFMS, 2021-I2M-1-066, 2017-I2M-4-002, 2021-I2M-1-019, 2017-I2M-1-001), the National Natural Science Foundation of China (81972311, 82141127, 31970794, ), the State Key Project on Infection Diseases of China (2017ZX10201021-007-003), the Non-profit Central Research Institute Fund of Chinese Academy of Medical Sciences (2019PT310026), Sanming Project of Medicine in Shenzhen (SZSM202011010), and the State Key Laboratory Special fund from the Ministry of Science (2060204).